PECULIARITIES OF SURFACE LOCALIZED PLASMONS IN THE METAMATERIALS - Vardanyan, A.Yu. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2012)
The possibility of localized surface plasmons formation in spherical structure based on metamaterials, with both the positive and negative dielectric constants, are considered. In contrast to ordinary localized surface plasmons, where the field decreases according to the power law with increasing distance from metallic nanoparticles, in case of strongly localized surface plasmons the field decreases according to the exponential law. Owing to that good preconditions are created for formation of structures with controllable parameters, where the wave energy is concentrated within nanometric ranges as is the case in atoms.